Molecular Docking Appraisal of Phytochemicals as Potential Inhibitors of PI3K/Akt Pathway for Breast Cancer Treatment - Magdalene Eno Effiong; Mercy Bella-Omunagbe; Israel Sunmola Afolabi; Shalom Nwodo Chinedu (Bioinformatics and Biology Insights)
Introduction: Breast cancer (BC) is a heterogeneous disease involving a network of numerous extracellular signal transduction pathways. The phosphoinositide 3-kinase (PI3K)/serine/threonine kinase (Akt)/mechanistic target of rapamycin (mTOR) pathway is crucial for understanding the BC development. Phosphoinositide 3-kinase, phosphatase and tensin homolog (PTEN), mTOR, Akt, 3-phosphoinositide-dependent kinase 1 (PDK1), FoxO1, glycogen synthase kinase 3 (GSK-3), mouse double minute 2 (MDM2), H-Ras, and proapoptotic B-cell lymphoma 2 (BCL-2) family protein (BAD) proteins are key drivers of this pathway and potential therapeutic targets. Pleurotus ostreatus is an edible mushroom that is rich in flavonoids and phenols that can serve as potential inhibitors of proteins in the PI3K/Akt/mTOR pathway. Aim: This study evaluated the anticancer properties of P ostreatus through a structure-based virtual screening of 22 biologically active compounds present in the mushroom. Method: Model optimization was carried out on PI3K, PTEN, mTOR, Akt, PDK1, FoxO1, GSK-3, MDM2, H-Ras, and BAD proteins in the PI3K/Akt/mTOR pathway and molecular docking of compounds/control inhibitors in the binding pocket were simulated AutoDock Vina in PyRx. The drug likeness, pharmacokinetic, and pharmacodynamic features of prospective docking leads were all anticipated. Result: Several potent inhibitors of the selected key driver proteins in PI3K/Akt/mTOR pathway were identified from P ostreatus . Ellagic acid with binding affinities of −8.0, −8.0, −8.1, −8.2, −6.2, and −7.1 kcal/mol on PI3K, Akt, PDK1, GSK-3, MDM2, and BAD, respectively, had better binding affinity compared with their reference drugs. Likewise, apigenin (−7.8 kcal/mol), chrysin (−7.8 kcal/mol), quercetin (−6.4 kcal/mol), and chlorogenic acid (−6.2 kcal/mol) had better binding affinities to PTEN, mTOR, FoxO1, and H-Ras proteins, respectively. Conclusion: Ellagic acid, apigenin, luteolin, quercetin, chlorogenic acid, chrysin, and naringenin phytochemicals are seen as the better lead molecules due to their ability to strongly bind to the proteins under study in this pathway. Analogs of these compounds can also be designed as potential drugs.